2009
DOI: 10.1111/j.1749-771x.2009.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Urine cytology is an unnecessary expense in the evaluation of adult haematuria

Abstract: Patients with microscopic and macroscopic haematuria undergo a series of investigations: the upper tracts are investigated with radiological investigations, the lower urinary tract with cystoscopy; urine is sent for microscopy, culture and sensitivity and cytological analysis. The aim of this study is to evaluate the role of urine cytology in adult patients with haematuria. A total of 6060 voided urine cytology specimens obtained from adults over the age of 18 who presented with haematuria in a single centre. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…We have previously shown that urine cytology is expensive, slows the patient pathway, lacks sensitivity and is unreliable at both detecting and excluding neoplasms of the urinary tract with a positive predictive value of only 41% (Turner et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that urine cytology is expensive, slows the patient pathway, lacks sensitivity and is unreliable at both detecting and excluding neoplasms of the urinary tract with a positive predictive value of only 41% (Turner et al , 2009).…”
Section: Introductionmentioning
confidence: 99%